Shell Texture Functions - Chen, Yanyun; Tong, Xin; Wang, Jinpeng; Lin, Steve; Guo, Baining; Shum, Harry (ACM Transactions on Graphics (TOG) - Proceedings of ACM SIGGRAPH 2004, 2004)
We propose a texture function for realistic modeling and efficient rendering of materials that exhibit surface mesostructures, translucency and volumetric texture variations. The appearance of such complex materials for dynamic lighting and viewing directions is expensive to calculate and requires an impractical amount of storage to precompute. To handle this problem, our method models an object as a shell layer, formed by texture synthesis of a volumetric material sample, and a homogeneous inner core. To facilitate computation of surface radiance from the shell layer, we introduce the shell texture function (STF) which describes voxel irradiance fields based on precomputed fine-level light interactions such as shadowing by surface mesostructures and scattering of photons inside the object. Together with a diffusion approximation of homogeneous inner core radiance, the STF leads to fast and detailed raytraced renderings of complex materials.